Trastuzumab-induced cardiotoxicity: testing a clinical risk score in a real-world cardio-oncology population - Rushton, M; Johnson, C; Dent, S (Université d'Ottawa | University of Ottawa, 2017)
Trastuzumab has improved survival for women with her2-positive breast cancer, but its use is associated with an increased risk of cardiotoxicity. With increased survivorship, the long-term effects of cancer treatment are an important consideration for clinicians and patients. We reviewed the current literature on predicting trastuzumab-related cardiotoxicity and tested a clinical risk score (crs) in a real-world breast cancer population to assess its utility in predicting permanent cardiotoxicity.
Keywords: Breast cancer; cardiotoxicity; heart failure; trastuzumab